Measurement of radiative shock properties by X-ray Thomson scattering - Visco, A; Drake, R; Glenzer, S; Döppner, T; Gregori, G; Froula, D; Grosskopf, M (2012)
X-ray Thomson scattering has enabled us to measure the temperature of a shocked layer, produced in the laboratory, that is relevant to shocks emerging from supernovas. High energy lasers are used to create a shock in argon gas which is probed by x-ray scattering. The scattered, inelastic Compton feature allows inference of the electron temperature. It is measured to be 34 eV in the radiative precursor and ∼60eV near the shock. Comparison of energy fluxes implied by the data demonstrates that the shock wave is strongly radiative. © 2012 American Physical Society.